Obligatoriedad de la responsabilidad social empresarial como mecanismo para proteger los derechos de los stakeholders frente al ejercicio del derecho constitucional de la libertad de empresa, perú-2013 - Zapata Jáuregui, Nathaly (2014)
Undoubtedly, the profound changes that have occurred in society worldwide in recent decades have created an urgent need to review and modify some aspects of business, so that Corporate Social Responsibility is gaining a presence increasingly important in the business sector. In that sense, the so-called Corporate Social Responsibility has become one of the key points that any public or private entity may overlook, including those native to countries which have not yet released the scope of the same. Such is the case of Peru, where there is still no corporate conscience or a legal framework to meet current requirements regarding Corporate Social Responsibility, as happens in other countries. To not go that far, in other Latin American countries such as Costa Rica, Argentina, Colombia and Chile, and there have been attempts to provide compulsory for Corporate Social Responsibility through a legal framework, some of them presenting bills. While we find ourselves behind in the development and study of this research topic, through this thesis we want to be one step closer to coating with due importance to corporate social responsibility in our country. In this context, this research aims to demonstrate the current situation in the regulation of Corporate Social Responsibility is in Peru and in the world. In addition to analyzing the need to make mandatory Corporate Social Responsibility as a mechanism to protect the rights of stakeholders against the exercise of the right to Free Enterprise. It also aims to demonstrate that it is possible to satisfy consumers and minimize negative while the corporate profits are maximized environmental impacts